ANALISIS STRATEGI PENJUALAN MADU PADA UMKM DI KABUPATEN SUMBAWA (Studi Pada UMKM Madu UD. Sari Bunga di Desa Kelungkung) - I Ismawati; Nining Sudiyarti; Della Delia Febriani (Fakultas Ekonomi dan Manajemen, 2021)
The purpose of this study was to know the sales strategy implemented by micro small and medium enterprises (UMKM) of Sumbawa Honey. The type of this study was descriptive qualitative. The data used in this study were primary data and secondary data. Primary data in this study was data obtained directly from UMKM of UD. Sari Bunga, Kelungkung village, Batu Lanteh sub-district, while the secondary data in this study was obtained from the Sumbawa UMKM gallery. Informants in this study were the owners and employees of UMKM UD. Sari Bunga Klungkung village, Batu Lanteh sub-district. Data collection techniques used were through interviews, observation and documentation. The data analysis tool used was SWOT analysis. Results of study showed that the marketing strategy used by UD. Sari Bunga was used E-commerce. Marketing strategy through e-commerce at UD Sari Bunga was in the growth quadrant. In this growth quadrant was very favorable for UMKM of UD Sari Bunga marketing. Furthermore, the sales strategy for UMKM of UD. Sari Bunga had strengths and weaknesses. The strength of UMKM UD. Sari Bunga Klungkung using E-commerce was that the packaging of UD Sari Bunga was good and attractive and the sales process had been done using facebook, then the weakness was inadequate human resources because there were not training and counseling done by the government in developing product of UMKM and also the dependence of honey bee farmers on the availability of bees honey provided by nature in the forest.